Galectin-10 and Charcot-Leyden Crystals in Chronic Rhinosinusitis with Nasal Polyps: Pathogenetic Insights and Clinical Implications - Bartłomiej Kamiński; Dominika Ochab; Janusz Kopczyński; Piotr Łacwik; Cezary Pałczyński (Diagnostics, 2026)
Chronic rhinosinusitis with nasal polyps (CRSwNP) is a heterogeneous inflammatory disease in which type 2 inflammation predominates in most patients in Western populations. Galectin-10 (Gal-10) and Charcot-Leyden crystals (CLCs), linked to eosinophil activation, cytolysis and eosinophil extracellular trap cell death (EETosis), have emerged as potential biomarkers and mediators of eosinophilic inflammation. This narrative review summarises current evidence on their biological role and clinical relevance in CRSwNP. The literature was identified through searches of PubMed/MEDLINE, Web of Science and Google Scholar, with emphasis on mechanistic studies, clinical investigations and recent evidence concerning type 2 inflammatory airway diseases. Available evidence suggests that Gal-10 and CLCs are associated with eosinophil activation and may contribute to persistent type 2 inflammation through epithelial injury, increased mucus viscosity, impaired mucociliary clearance, tissue remodelling and inflammatory amplification. Gal-10/CLCs may have value as investigational biomarkers of disease activity, postoperative recurrence and response to biologic therapy. Current biologics may indirectly modulate the Gal-10/CLC pathway by reducing eosinophil survival, recruitment or activation, although direct evidence remains limited. Gal-10 and CLCs are promising investigational biomarkers and mechanistically plausible therapeutic targets in CRSwNP. However, clinical application is limited by the lack of standardised analytical methods, validated cut-off values and prospective studies demonstrating incremental value beyond established biomarkers. Further research is required to clarify their role in stratification, prognosis and monitoring of biologic therapy.